The Effect of Cohesive Debonding Elimination on Enhancing the Flexural Performance of Damaged Unbonded Prestressed Concrete Girders Strengthened Using NSM CFRP (Journal of Engineering, 2023)
This manuscript studied the effect of U-CFRP wrapped sheet anchorage on the flexural performance of unbonded post-tensioned PC members subjected to partial strand damage and strengthened using CFRP Near-Surface Mounting techniques. The program includes six girders as a control girder, a girder with strand damage of 14.2%, and four girders strengthened by CFRP laminates using the NSM technique with and without U-CFRP wrapped sheet anchorages. The testing results show that the strand damage of 14.2% has reduced the flexural strength of the girder by 5.71%. The NSM-CFRP laminate has a significant effect on flexural strength by 17.4%. On the other hand, the application of end U-CFRP wrapped sheet anchorages improves flexural strength by 27.97% and enhances ductility. The intermediate and successive U-CFRP sheet anchorages increase the flexural strength by 36.56% and 32.61%, enhancing the stiffness at all loading stages and improving the ductility. Semiempirical equations were developed to determine the actual stress of unbonded strands considering the effect of U-FRP-wrapped anchorages.